Problematika Pembelajaran Tatap Muka Terbatas (PTMT) dalam Menulis Resensi Novel pada Siswa Kelas XII SMAN Ploso Jombang - Aminatar Rofiyah (Journal of Education and Learning Sciences, 2022)
This study aims to describe the problems of limited face-to-face learning (PTMT) in writing novel reviews and their solutions to class XII students of SMAN Ploso. This type of research is a qualitative research with descriptive method. The results showed that there were problems which included 1) problems with limited face-to-face learning tools, 2) problems in the delivery of limited face-to-face learning materials, 3) problems in classroom management, and 4) problems with techniques and assignments. While the solutions that can be given are 1) students will be given a more effective learning flow, 2) students will be given learning methods and media that are in accordance with the material and needs of students, 3) students will be given more attention with personal guidance and change learning techniques and tactics , and 4) students will be directed in more detail about the structure, spelling, and steps of writing a novel review text.